Meridionalismo e scuola nell’Italia unita - Trebisacce, Nicola (Studi sulla Formazione/Open Journal of Education, 2018)
For some years, the Southern question, which has always nurtured the country's political and cultural debate during the 150 years of unitary history, is no longer the focus of governments’ attention or the reflection of the intellectual classes. Starting from this fact, the writing intends to restore centrality to the debate on meridionalism by reconstructing the most significant historical moments of the relationship between the school and the meridionalism, starting from the post-unification period.